Erythroderma as first sign of lung cancer - Ana G. Lopes; Maria J. Guimarães; Catarina Cerqueira; Joana Gomes; Celeste Brito (Sociedade Portuguesa de Dermatologia e Venereologia, 2022)
Erythroderma, or generalized exfoliative dermatitis, is a rare inflammatory disorder characterized by generalized erythema, involving more than 90% of the body surface area, accompanied by a variable degree of scaling. It may be the clinical presentation of several cutaneous or systemic diseases and it is frequently challenging to find the underlying cause. Our case focuses on a 76-year-old male patient that was referred to our department due to generalized erythroderma and diffuse alopecia, developing over the last 4 months. He presented with erythematous papules and nodules, some of them covered with sticky scales. Skin biopsy was compatible with drug eruption. Due to an inadequate response to treatment and typical B symptoms, further imagiologic studies were performed. Ultimately he was diagnosed with non-small cell lung cancer. This case shows the need to search for a neoplasm in patients presenting with erythroderma, particularly in the presence of systemic symptoms.